Scientific animations without borders: cell-phone videos for cowpea farmers - Bello, J.; Seufferheld, F.; Agunbiade, T.; Steele, L.D.; Guillot, D.; Ba, Malick N.; Binso-Dabire, C.L.; Baoua, I.; N'Diaye, M.; Tamo, Manuele; Pittendrigh, R. (International Institute of Tropical Agriculture, 2012)
Over the past several decades, researchers and extension agents have described methods that cowpea farmers can use to reduce insect damage to the cowpea crop in the field and in storage. Some of these methods, which are based on both scientific research and indigenous knowledge, are currently being used in local, regional , national, and transnational extension programs. Cowpea farmers in Africa and other developing regions, however, often remain unaware of the methods based on scientific research because the farmers are low-literate and the information may be available only in a written form. Farmers also may remain unaware of methods based on indigenous knowledge because such information usually remains local. These problems are exacerbated by the limited resources of extension programs. Here we describe how pest control information in the form of short animations can be transferred to low-literate farmers via cell-phone technology and through the World Wide Web. Voice overlays in a diversity of languages can be easily added to these animations so that ideas can be efficiently shared across cultural groups. The animated videos, which are being developed by the organization Scientific Animations Without Borders™ (SAWBO), can be viewed on cell phones and can be transmitted between cell phones using Bluetooth® technology.